MISOGINI DALAM KOMENTAR DI AKUN INSTAGRAM @CLARAANDJAVI: KAJIAN SEMANTIK - Tasya Febrianty (Indonesian Journal of Linguistics, 2000)
Misogyny is one of the forms of hate speech against women that often appears on social media, including in comments on Instagram accounts. This research aims to identify the forms of misogyny in the comments of @claraandjavi's Instagram account and analyze its conceptual meaning. The method used in this research is descriptive qualitative method with data sources in the form of comments containing elements of misogyny and data collection techniques in the form of  observation and documentary evidence of comments in the form of screenshots. The results showed that there were comments containing misogyny utterances, such as several comments “dia cowo ya?”, “rata tembok”, and “nanti biar di modif sendirif”. This shows that the comments posted have conceptual meanings that relate to women's value of their physical appearance and reflect the prevailing social construction of gender related to unrealistic beauty standards and the comments also contribute to reinforcing the objectification of women's bodies, women are often judged based on their body or physical appearance. That physical appearance is everything for women and women must have a certain body shape to be considered attractive, without regard to ability or personality.aspects of ability or personality.